Ferroresonance in capacitive voltage transformer (CVT) due to breaker opening / Shakil Ahamed Khan - Khan, Shakil Ahamed (2015)
Ferroresonance incidences in electrical power system have been commonly regarded as unexplained phenomenon due to its relatively rare frequency of occurrence which is not critical by the utility engineers. As a result, research conducted in this area is limited and the awareness on ferroresonance is relatively low amongst the utility engineers. However, as the electrical system evolves, its complexity increases in line with the increasing risk of ferroresonance. Ferroresonance gained prominence only in the recent decade, when it has been reported to cause damaging consequences to power equipment. Several literatures had concerning reported practical encounters of ferroresonance which led to equipment failures and electrical blackout. It must be noted that most of the literatures concentrated on ferroresonance in power transformer only. In contrast, this research will place ferroresonance in capacitive voltage transformer (CVT) as the main focus. It is demonstrated in this research that ferroresonance can also occur in CVT due to circuit breaker switching. Various ferroresonance suppression techniques have since been proposed as ferroresonance mitigation solutions in CVT. This research presents a new technique for detection and mitigation of the ferroresonance phenomenon in CVT. In addition, the transient performance of CVT and ferroresonance mitigation performance with the proposed new technique is also compared with other existing ferroresonance suppression techniques. EMTP-RV simulation results demonstrate that, the transient response for a CVT with the proposed ferroresonance suppression circuit (FSC) is much better than conventional active and passive FSCs. The accuracy of the proposed ferroresonance detection and mitigation technique is verified through comparison of the laboratory test (Hardware-in-the-Loop (HIL) real-time simulations) results and with those obtained from EMTP-RV simulation results. Closed-loop testing is performed using real time digital simulator (RTDS). The experimental results demonstrate that the developed technique can accurately detect the phenomenon of ferroresonance in CVT and can suppress ferroresonance faster than other conventional techniques.